3D texture parameters for wear scars after severe regime. Issue 3 (30th December 2021) - Deleanu, Lorena; Ionescu, Traian Florian; Cristea, George Catalin; Suciu, Cornel Camil; Georgescu, Constantin
Abstract : Purpose: This paper aims to present an analysis of several 3 D texture parameters for the entire wear scars obtained in severe regime, on a four-ball tester. The aim of this analysis is to correlate the tribological parameter as wear scar diameter to texture parameters. Design/methodology/approach: Tested lubricants were rapeseed oil, rapeseed oil additivated with 1% Wt nano TiO2 and rapeseed oil additivated with 1%Wt nano ZnO. The severe regime was applied for 1400 rpm and for loads increasing in steps of 50 N, from 500 to 900 N. Several analyzed roughness parameters (height parameters and functional ones) could be related to the evolution of a wear parameter, the wear scar diameter. Comparing the values for neat rapeseed oil and additivated variants, the texture parameters allow for evaluating if the additives protect or not the worn surfaces. Findings: Measurements pointed out two groups of roughness parameters: one that has an evolution depending on wear scar diameter (WSD) and load (Sa, St, functional parameters) and one including Ssk that has shown no dependence on load and WSD. Also, the functional parameters Spk and Svk follow in a similar manner the wear parameter, WSD, but Sk is the least dependent on load. For the highest load, amplitude parameters such as Sa and St are following the tendency of WSD. Each lubricant has its particular correlation between wear parameters and texture quality, expressed by the help of a set of roughness parameters. Research limitations/implications: Such studies help tribologists to rank lubricants based on a combined analysis with wear parameters and texture parameters. Practical implications: The results allow for evaluating new formulated lubricants. Originality/value: The study on the quality on worn surfaces introduces the original idea of analyzing the entire wear scar surface (approximated by an ellipse with the axes as those experimentally measured) by the help of a set of 3 D roughness parameters.